SEA VOYAGES AND OCCUPANCIES OF MALAYAN PEOPLES AT THE WEST COAST OF SOUTH SULAWESI - Muhlis Hadrawi (Hasanuddin University, 2018)
This paper discussesthe sea voyages and trades in relation to the history of Malayan occupancies at West Coast of South Sulawesi in fifteenth century when Bugis and Makassar kingdoms started to emerge. This research used philological approach with manuscripts (lontara) as primary data sources. The results of this research suggests that the establishment of local ports such as Suppa’, Siang, Tanete, Kalukubodoa, and Sanrabone along the west coast of South Sulawesi since the fifteenth century indicates the initial periods of kingdoms’ maritime activities in South Sulawesi. In sixteenth century, these sailing and trading activities continued to show their progress which was marked by the establishment of networks and relationships between Bugis and Makassar kingdoms with other areas at Nusantara such as Malacca, Pahang, Minangkabau, Patani, and Champa. It was proved, then, that these sailing and trading activities have become a crucial factor which led to the establishment of cooperation and social integration between Bugis-Makassar peoples and Malayan peoples who came from Malay Peninsula and Sumatera. Malayan traders already sailed to Sulawesi since the fifteenth century and they were well accepted by Bugis and Makassar local peoples. These Malayan traders from social relation aspectwere accepted as residents, and even allowed to married with Bugis and Makassar peoples. In the long run this kind of intermarriage would integrate those Malayan into Bugis and Makassar.